PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS BINTALJARAHDAM DI KODAM JAYA KECAMATAN KRAMAT JATI JAKARTA TIMUR - Ikhfidh Fii Haasyabillah; Turah Slamet (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine how much influence Leadership Style and Work Motivation have on Employee Performance at the BINTALJARAHDAM Service at Kodam Jaya, the model used in this study is a quantitative descriptive method and the data collection technique uses a questionnaire, using 50 samples. And the analytical method used is multiple linear regression analysis, and t test and f test, to find out the independent variables that affect the dependent variable, in managing this data using the SPSS application program tool version 26.0. The results of multiple linear regression indicate that Leadership Style has a positive and significant effect on Employee Performance. Work Motivation has no significant effect on Employee Performance. Based on the results of the F test, it shows that Leadership Style and Work Motivation simultaneously have a significant effect on Employee Performance.